The role of contexts in supporting early statistical reasoning in data modeling (2023)
ABSTRACT: Data modeling is an essential activity in a data-driven society, but such a topic and how the context shapes it has received limited attention. This paper reports on research that investigated the role of context in supporting early statistical reasoning in the data modeling process. The data were collected throughout sessions in which young children (7 year-old) worked out problem activities designed to stimulate data modeling. The problem activities started by reading children’s story books purposefully created as a strategy to provide contexts of interest. The stories were inscribed within culturally relevant contexts in which the characters deal with data in different formats. The data modeling problem activities were closely related to the stories described within the books. Special attention was put into the actions of organizing, structuring, visualizing, and representing data and the role of the context in the data modeling process. The main results suggest that the context of the problem activities for the data modeling process seems to facilitate statistical reasoning in young children. Additionally, the context of the problem activities helped participants to develop strategies to identify attributes of data, assess the model created, make sense of the data, and make informal inferences.